2010
DOI: 10.1037/a0017180
|View full text |Cite
|
Sign up to set email alerts
|

Context effects on the processing of action-relevant object features.

Abstract: In 4 experiments, we investigated the effects of object affordance in reach-to-grasp actions. Participants indicated whether a depicted small or large object was natural or manmade by means of different object-grasping responses (i.e., with a power or a precision grip). We observed that the size of the depicted object affected the grasping kinematics (grip aperture) and the reach-onset times of compatible and incompatible actions. Additional experiments showed that the effect of perceived object size on motor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 46 publications
5
41
0
Order By: Relevance
“…In support of this claim, we note a recent study by Girardi, Lindemann, and Bekkering (2010), in which subjects were shown a priming picture consisting of a hand and an object, and were required to make a power or precision grasp to classify the object as manmade or animate. When the size of the object was consistent with the required grasp (e.g., precision grasp to classify a needle as manmade), the response was faster.…”
Section: Measuring Affordances To Objects In Canonical and Rotated Ormentioning
confidence: 69%
“…In support of this claim, we note a recent study by Girardi, Lindemann, and Bekkering (2010), in which subjects were shown a priming picture consisting of a hand and an object, and were required to make a power or precision grasp to classify the object as manmade or animate. When the size of the object was consistent with the required grasp (e.g., precision grasp to classify a needle as manmade), the response was faster.…”
Section: Measuring Affordances To Objects In Canonical and Rotated Ormentioning
confidence: 69%
“…In broad terms, the use of a tool (e.g., a pencil) would require the extraction of sensory information about object properties (light, rigid), which could be translated directly into appropriate motor outputs (grasping, writing). This direct route would allow humans to extract automatically the tool actions the objects aVord before intentions are formed (e.g., Tipper et al 2006;Tucker and Ellis 1998;Yoon et al 2010; for limitations and more discussions, see Anderson et al 2002;Girardi et al 2010;Phillips and Ward 2002;Osiurak et al 2010Osiurak et al , 2011. As discussed above, Witt et al (2005, Experiment 3) reported that people who hold a tool but do not intend to reach the targets do not perceive them to be closer.…”
Section: Discussionmentioning
confidence: 99%
“…ingly, MRs' detection of action possibilities is not so automatic, as agreed in the philosophical literature -indeed, the issue of automaticity of MRs is hotly debated in the neuroscientific literature, in which it is suggested that the task and the context are crucial in determining the ''behavior" of the MR (see Borghi & Riggio, 2015: 8;Girardi, Lindemann, & Bekkering, 2010; van Elk et al, 2014; cfr. with my footnote 18).…”
Section: The Many Facets Of Our Visuomotor Interactionsmentioning
confidence: 99%